High-resolution optoacoustic mesoscopy with a 24MHz multidetector translate-rotate scanner - Gateau, Jerome; Chekkoury, Andrei; Ntziachristos, Vasilis (Journal of Biomedical Optics, 2013)
Optoacoustic (photoacoustic) mesoscopy aims at high-resolution optical imaging of anatomical, functional, and cellular parameters at depths that go well beyond those of optical-resolution optical or optoacoustic microscopy i.e., reaching several millimeters in depth. The approach utilizes tomography to achieve ultrasonic-diffraction resolution and operates at high-ultrasound frequencies (20 to 200MHz) induced by few-nanosecond laser pulse excitation of tissues. We investigated here the performance of optoacoustic mesoscopy implemented at 24MHz center frequency and its ability to resolve optical absorption contrast in the mouse kidney ex vivo. The developed system achieved better than 30μm in-plane resolution and 110μm elevation resolution over a cylindrical volume of 9-mm diameter and 9-mm height. This unprecedented combination of resolution and depth was achieved by implementing a translate-rotate detection geometry and by tomographic reconstruction. The approach yielded images of optically absorbing structures with a level of detail never-before visualized in an intact mouse kidney and allows insights into their unperturbed architecture. We discuss the ability to offer multispectral acquisitions and enable in vivo imaging. © 2013 Society of Photo-Optical Instrumentation Engineers.
CRIS-Team Scopus Importer:2023-03-08
Keywords: optoacoustic mesoscopic scale linear array computed tomography high-frequency ultrasound